A SOCIOLINGUISTIC ANALYSIS OF THE INTERRELATION BETWEEN TABOO AND EUPHEMISM IN LINGUISTICS - Zaynab Azimjon qizi Shermamatova (Journal Park Publishing, 2025)
The language system is a complex phenomenon that reflects the social and cultural values, moral norms, and the level of culture within a society. One of the significant manifestations of this system is the transformation of taboo words into euphemisms, which clearly demonstrates the social and cultural functions of language. This article analyzes the process of euphemization of taboo words, exploring its connection with social, cultural, and psychological factors. Examples from both Uzbek and English languages are examined to highlight how the replacement of taboo expressions with euphemisms is closely related to human thinking, cultural development, and the social environment.
Keywords: Taboo, euphemism, language culture, sociolinguistics, culture, speech ethics, morality.